Overcome procrastination: Enhancing emotion regulation skills reduce procrastination - Eckert, Marcus; Ebert, David; Lehr, Dirk; Sieland, Bernhard; Berking, Matthias (Learning and individual differences, 2016)
In a first study, cross-sectional analyses indicated that ER skills and procrastination were associated and that these connections were mediated by the ability to tolerate aversive emotions. In a second study, cross lagged panel analyses showed that (1) the ability to modify aversive emotions reduced subsequent procrastination and that (2) procrastination affected the subsequent ability to tolerate aversive emotions. Finally, in a third study, a two-arm randomized control trial (RCT) was conducted. Results indicated that systematic training of the ER skills tolerate and modify aversive emotions reduced procrastination. Thus, in order to overcome procrastination, emotion-focused strategies should be considered. (C) 2016 The Authors. Published by Elsevier Inc.
Keywords: Procrastination; Emotion regulation; Emotion-focused intervention; Training; Procrastination; Emotion regulation; Emotion-focused intervention; Training